2008
DOI: 10.1111/j.1432-2277.2007.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Static cold storage preservation of ischemically damaged kidneys. A comparison between IGL-1 and UW solution

Abstract: Summary Especially in damaged organs, adequate organ preservation is critically important to maintain viability. Institut Georges Lopez‐1 (IGL‐1) is a new preservation solution, with an extracellular sodium/potassium ratio and polyethylene glycol as a colloid. The influence of warm and cold ischemia was evaluated in a rat Lewis–Lewis transplant model with a follow up of 14 days. Eight groups of donation after cardiac death donor kidneys were studied with warm ischemia of 0 and 15 min followed by 0‐ or 24‐h col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…We chose 15 and 30 min for the duration of WI time in this animal model, as we had previously demonstrated that the combination of 15 min WI and 24 h CS results in a seriously damaged kidney graft, leading to delayed graft function after transplantation [9]. As NR is most interesting in the uncontrolled DCD (Maastricht categories I and II) [10] setting that will lead to severely damaged kidneys, we deliberately chose not to test the method on kidneys that have sustained only mild ischemic injury.…”
Section: Methodsmentioning
confidence: 99%
“…We chose 15 and 30 min for the duration of WI time in this animal model, as we had previously demonstrated that the combination of 15 min WI and 24 h CS results in a seriously damaged kidney graft, leading to delayed graft function after transplantation [9]. As NR is most interesting in the uncontrolled DCD (Maastricht categories I and II) [10] setting that will lead to severely damaged kidneys, we deliberately chose not to test the method on kidneys that have sustained only mild ischemic injury.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies [9,11,12,27] have also demonstrated the efficacy of PEG in liver, kidney, lung and pancreas preservation in experimental models and clinical trials. Recently PEG has been added to several newly developed preservation solutions, such as Polysol (PEG35 KDa, 20 g/L), SCOT (Solution de Conservation des Organes et des Tissus) solution (PEG20 KDa, 30 g/L), and IGL-1 (Institut Georges Lopez) solution (PEG35 KDa, 1 g/L) [6,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics render IGL-1 suitable for abdominal organ preservation. 7, 8, 9, 10, 11 However, the mechanisms by which IGL-1 protects against ischemia reperfusion (I/R) injury and maintains cell viability are unclear. Accumulating evidence suggested perturbations at the endoplasmic reticulum (ER) as novel subcellular effectors, possibly involved in the promotion of cell death during cold organ preservation.…”
mentioning
confidence: 99%